Sandheden som fremmedlegeme? Helge Grell: Skaberordet og billedordet. - Toftdahl, Helmutt (Grundtvig-Studier, 1982)
Truth as a Foreign Body? The Creative Word and the Word as Image By Helge Grell. Reviewed by Hellmut Toftdahl. How and why is mankind able to speak truth about God? - That is the subject of this book, which addresses itself to theologians. Grell treats a large area of Grundtvig’s authorship from the period 1807-32, where he works his way out of speculative unified philosophy and the idealistic view of Christianity. For Grundtvig cognition of the creation concept and the word of God are very closely connected. Man is created in time and space and apprehends with the aid of his senses in images or imaginative thoughts. So the eternal and spiritual must reveal itself to man in temporal and sensuous images. Truth must have a body. On the basis of the material before him Grell analyses Grundtvig’s major dogma: God is at hand for mankind in the Word of God as Creator, Redeemer and Holy Spirit. Since Grundtvig is under the powerful influence of Schelling during this period, the book considers Schelling’s philosophy in a separate appendix. In his presentation of Grundtvig’s thought Grell emphasizes that Grundtvig accepts dualism as a condition for his understanding of existence and that mankind is unable to gain eternity through poetry and philosophy because of the Fall. One chapter deals with unpublished sermons from the beginning of the 1820’s. Grell sees them as an expression of the thoughts that Grundtvig later advanced with regard to the aim and content of sermons. The weakness in this method is that Grundtvig the poet does not receive his full due; for it is precisely in this period that Grundtvig gives free rein to the imagery in his sermons. The author is more on the wave-length of Grundtvig the analyser than Grundtvig the poetic preacher. He presents Grundtvig’s development as that of a systematic theologian and disregards his poetic development in the same period. Because the book stops at 1832 there is no explanation of the relationship between the young theorist and the older politician on the subject of the Church and cultural affairs. This lack has spurred the reviewer into a further consideration of Grundtvig as a preacher, particularly in the light of Søren Kierkegaard’s criticism. Toftdahl sees the essence of Grundtvig’s problem as a preacher lying in truth being subjected to the body’s conditions: that truth has to be mediated in time and space on given historical and political conditions. It therefore seems appropriate to put the preaching theories of the young Grundtvig into the perspective of the older Grundtvig’s major statements about the conditions God’s Word faces in the political reality of the Church and cultural affairs. At what points was Grundtvig a divinely-inspired preacher, and at what points was he, in the words of Kierkegaard, “a bellowing blacksmith” or a “jaunty, yodelling chap”? Later on in life Grundtvig was aware that not all salvation is legitimatelybased. There are words that create life; but there are also words that create something that is hardly distinguishable from life. What decides the case is the conscience, “which is Truth’s own witness in us about itse lf’ (Church Faith and School Teachings 1846) - (Kirke-Troen og Skole-Læren). In the same place Grundtvig distinguishes between “the Faith of Truth” and “the Faith of Falseness”. What is so exciting about Grundtvig as a preacher is to see how the preacher keeps a fairly tight rein on the poet, but without choking him. His genius is not that he had visions - every poet has them - but how he dealt with those visions so that they benefitted others as well as himself. Solidarity with the fellowship of baptism and Holy Communion is the prerequisite for his calling his inspired moments “true”. It is a delicate balance between what is basic and what is vulgar. He analyses this in Elementary Christian Teachings 1855-61 (Den Christne Børnelærdom), and it is reflected everywhere in his political work on cultural affairs. The cardinal point in Grundtvig’s theory of preaching and in his political programme was a separatism between the Church, the State and the School. He wanted a society in which growth of consciousness, politics and education all exist freely and independently of each other. Grundtvig thus represents an alternative to our present way of thinking, in which politics infiltrates both education and religion. With Grundtvig Truth’s body is present, in contrast to abstract ideologies: “these French and German free-hand drawings of castles in the air”, he calls them, protesting against the use of ideologies as a substitute for lost religious feeling. Only through the greatest possible comprehensiveness in education and the greatest possible political freedom can Truth be given fair conditions of existence; the Lie will reveal itself. A relevant cultural battle on Grundtvig’s terms must therefore consist of fighting ideological infiltration wherever it is to be found in the politics of the Church and of education. In a thoroughly politicised, technocratic and authoritarian world it is perhaps the individual congregation that is the last refuge for the scruples that the individual in Grundtvig and Kierkegaard’s time was still strong enough to manage as an isolated individual. The collective defence of the Truth of the message of conscience and love may be the Grundtvigian alternative to the brave new world. In a technocratic society Truth’s body will be diagnosed as a foreign body: either an insignificant splinter in the machine or an irritating mistake in the control-room. This will depend on what sort of impetus the Grundtvigian alternative to the brave new world is given. But a body will not let itself be quietly choked. It reacts violently when it is threatened. Often the will to live grows with the threat. The corporality of Truth adds to the gospel what is so characteristic of Grundtvig, namely the battle motif. The gospel is not merely a dogmatic or an aesthetic problem, but a vital, existential problem. It is in battle that Truth proves its life-power against the facile truth, the “castles in the air” of ideologies.